Comprehensive Outcomes of the Keystone Design Perforator Island Flap: A Prospective Study of 121 Consecutive Cases - Pejkova, Sofija; Georgieva, Gordana; Tusheva, Sofija; Jovanovska, Katerina; Mladenovska, Stefania Azmanova; Nikolovska, Bisera; Srbov, Blagoja (Archives of Plastic Surgery, 2025)
The Keystone Design Perforator Island Flap (KDPIF), developed by Behan in 2003, has significantly impacted reconstructive surgery. This technique utilizes angiotomes, which integrate vascular, dermatomal, neural, and lymphatic networks, providing various approaches for complex reconstructions.This study enhances the initial PACE framework (Pain, Aesthetic appearance, Complication rates, Economic feasibility) by adding “S” for Sensibility, creating the PACES framework to include sensory improvements in the assessment.Our retrospective analysis included 121 patients over 51 months, primarily with defects from skin malignancies (66.9%) and chronic wounds (16.5%), mainly on the trunk (51.2%). The average age was 56.2 years, with males comprising 73.6% of the cohort.Outcome measures included pain, assessed using the Visual Analog Scale at 1 and 12 months postoperatively, revealing a significant reduction in pain. Aesthetic outcomes were evaluated through the Manchester Scar Scale, showing notable improvements in scar appearance. Complication rates were low, indicating the safety of the flap in this series. Economic efficiency was assessed by operative time and hospital stay, with shorter durations indicating cost-effectiveness.Sensory outcomes, measured with the Postoperative Flap Sensitivity Self-Assessment Questionnaire, showed substantial gains in sensory function, enhancing patients' quality of life.The PACES framework facilitated a comprehensive evaluation of KDPIF, confirming its effectiveness across various defect types and patient populations. Our findings support the wider adoption of KDPIFs for reconstructive purposes, alongside ongoing efforts to optimize patient outcomes and functionality.
Keywords: Keystone flap; reconstruction; KDPIF; perforator flap; sensibility